Diverse cooling effects of green space on urban heat island in tropical megacities - Li, Chunbo; Lu, Linlin; Fu, Zongtang; Sun, Ranhao; Pan, Luyang; Han, Liying; Guo, Huadong; Li, Qingting (Frontiers in Environmental Science, 2022)
Cities in tropical regions are experiencing high heat risks by overlaying the urban heat island(UHI) effect. Urban green space (UGS) can provide local cooling effect and reduce UHI. However, there still lack a comprehensive exploration of the characteristics of UHI and cooling effect of UGS due to high cloud coverage and limited number of available remote sensing observations. In this study, the enhanced spatial and temporal adaptive reflectance data fusion method was employed to develop an enhanced land surface temperature data in winter seasons in three tropical megacities, Dhaka, Kolkata, and Bangkok. The spatiotemporal variations of surface urban heat island (SUHI) were explored from 2000 to 2020 with a five-year interval. The optimal size of UGS associated with its cooling effects was assessed by using the threshold values of efficiency (TVoE). The relationship between the intensity and range of urban cooling island(UCI) and four landscape metrics of green space patches, total area (P_Area), shape index (P_SI), normalized differential vegetation index (P_NDVI), and land surface temperature (P_LST), were analyzed. The results show that the average SUHI intensity increased by 0.98°C, 1.42°C, and 0.73°C in Dhaka, Kolkata, and Bangkok, respectively. The optimal size of green space is 0.37 ha, 0.77 ha, and 0.42 ha in Dhaka, Kolkata, and Bangkok, respectively. The maximum intensity of UCI ranges from 4.834℃ in Bangkok to 8.071℃ in Kolkata, and the maximum range of UCI varies from 300m in Bangkok to 420m in Kolkata. The P_NDVI, P_LST and P_Area had significant positive or negative effects on UCI intensity, respectively. This study provides useful information for developing effective heat mitigation and adaptation strategies to enhance climate resilience in tropical cities.